Equivalent circuit modeling and analysis of aerodynamic vortex-induced piezoelectric energy harvesting - Jia, Jinda (2022)
Low-speed wind energy has potential to be captured for powering micro-electro-mechanical systems or sensors in remote inaccessible place by piezoelectric energy harvesting from vortex-induced vibration. Conventional theory or finite-element analysis mostly considers a simple pure resistance as interface circuit because of the complex fluid-solid-electricity coupling in aeroelastic piezoelectric energy harvesting. However, the output alternating voltage should be rectified to direct voltage to be used in practical occasions, where the theoretical analysis and finite-element analysis for complex interface may be cumbersome or difficult. To solve this problem, this paper presents an equivalent circuit modeling (ECM) method to analyze the performance of vortex-induced energy harvesters. Firstly, the equivalent analogies from the mechanical and fluid domain to the electrical domain are built. The linear mechanical and fluid elements are represented by standard electrical elements. The nonlinear elements are represented by electrical non-standard user-defined components. Secondly, the total fluid-solid-electricity coupled mathematical equations of the harvesting system are transformed into electrical formulations based on the equivalent analogies. Finally, the entire ECM is established in a circuit simulation software to perform system-level transient analyses. The simulation results from ECM have good agreement with the experimental measurements. Further parametric studies are carried out to assess the influences of wind speed and resistance on the output power of the alternating circuit interface and the capacitor filter circuit. At wind speed of 1.2 m s-1, the energy harvester could generate an output power of 81.71 μW with the capacitor filter circuit and 114.64 μW with the alternating circuit interface. The filter capacitance is further studied to ascertain its effects on the stability of output and the settling time.